MEDB-69. Clinical and molecular meta-analysis of three major medulloblastoma clinical trials (ACNS0331, SJMB03, ACNS0332) uncovers novel strategies to improve risk-stratified therapy. (3rd June 2022) - Smith, Kyle S; Billups, Catherine A; Dhanda, Sandeep K; Bihannic, Laure; Vasilyeva, Aksana; Li, Yimei; Michalski, Jeff M; Olsen, James M; Leary, Sarah; Fouladi, Maryam; Gajjar, Amar; Onar, Arzu; et al.
Abstract: BACKGROUND: Given the vast molecular heterogeneity present within medulloblastoma (MB) and considerable differences in therapy, we performed a meta-analysis of three large, recently published, prospective clinical trials (ACNS0331, SJMB03, ACNS0332) comprising 898 children with newly-diagnosed MB to shape future therapy. METHODS: Molecular subgroups, subtypes, and copy number variations were uniformly procured from DNA methylation profiles and mutations from next-generation sequencing. Patients were stratified into six clinically homogeneous groups for cross-trial comparisons: (1) ACNS0331_LDCSI - patients with non-metastatic (M0), non-residual (R0), non-anaplastic MB treated with low-dose (LD) craniospinal irradiation(CSI); (2) ACNS0331_SDCSI - patients with M0R0 non-anaplastic MB treated with standard-dose(SD) CSI; (3) SJMB03_SDCSI - patients with M0R0 non-anaplastic MB treated with SDCSI; (4) SJMB03_HDCSI - patients with metastatic (M+) MB treated with high-dose (HD) CSI; (5) ACNS0332_HDCSI - patients with M+ MB treated with HDCSI; (6) ACNS0332_HDCSI_Carbo - patients with M+ MB treated with HDCSI and carboplatin. RESULTS: 803 (WNT=125, SHH=122, G3=189, G4=367) of 898 patients formed the cohort. No significant difference was observed between the event-free survival (EFS) from ACNS0331_SDCSI and SJMB03_SDCSI or from SJMB03_HDCSI and ACNS0332_HDCSI when analyzed as a whole or by subgroup. ACNS0331_LDCSI outcome was inferior to the combined ACNS0331_SDCSI + SJMB03_SDCSI cohorts (p<0.001) and in G3 (p=0.030). ACNS0332_HDCSI_Carbo EFS was superior to ACNS0332_HDCSI + SJMB03_HDCSI only in G3/G4_subtype III (p=0.045). Additional molecular risk factor analysis identified M0R0 G3/G4_subtype VII and SHH without high-risk features as very low risk (>90% EFS) and M0R0 G3/G4_subtype III as high risk (<40% EFS). CONCLUSION: The comparable results observed across trials presents a welcome opportunity to reduce toxicity by eliminating excessive doses of chemotherapy (i.e. vincristine, cisplatin, and cyclophosphamide) from therapy. Furthermore, these results support molecularly driven risk classification as the means for a better, more-refined, treatment stratification.